Temporal and spatial distribution of semicarbazide in western Laizhou Bay. Issue 1 (15th November 2016) - Tian, Xiuhui; Xu, Yingjiang; Song, Xiukai; Gong, Xianghong; Liu, Yihao; Zhou, Quanli; Wang, Zhongquan; Xia, Chuanhai
Abstract: Semicarbazide (SEM), an industrial raw material and the marker residue of nitrofurazone as a veterinary drug, has become a new type of marine pollutant. A standard method (ultra-performance liquid chromatography–tandem mass spectrometry, UPLC–MS/MS) was used to analyze SEM in seawater, sediment, and shellfish. A series of sections and stations were set up in radical distribution in western Laizhou Bay, with six voyages and 150 monitoring samples. The concentrations of SEM in seawater and shellfish were 10 − 11 and 10 − 10 kg/L, respectively, and no SEM was detected in the sediment. Distribution characteristics at each state, temporal and spatial trends, multivariate analyses, and the causes were analyzed to assess the pollution level, which aimed to offer a database for drafting the national baseline values of SEM in seawater and sediment in future. The data obtained could be used for integrated watershed management of marine environment and economic activities for constructing a blue economic zone of Shandong Peninsula in China. Highlights: Method for determination SEM in seawater and sediment by UPLC-MS/MS was developed and validated for the first time. No literature was on SEM pollution in ocean in China even the world. Our team was the first to do such research and analyze distribution characteristics. Explore the relation between shellfish detected SEM without using NFZ and content of SEM in the environment. Based on early warning values of SEM established in other studies of our team, pollution level of SEM was evaluated.